Auditoría financiera y su incidencia en el control contable y financiero de la red educativa hispana rural “Alberto Mena Cueva”, cantón El Empalme, año 2012 - Litardo Villamar, Sully Paola (2015)
Once developed the research we were able to obtain the following criteria; the rules and laws in force in the Ecuador related with the public finances the sets the Ministry of Finance, once developed the analysis of all those provisions issued to the management of the administrative and operating processes of the entity can be conclude that the organization complies with all the provisions that emit the control agencies. All those procedures that involve the accounting and financial control of public institutions in relation to financial and technical resources that are assigned are issued and regulated by the Comptroller General of the State; the result of the Internal Control questionnaire applied, demonstrated the weaknesses that keep the institution at the time of the day-to-day operations that are presented on the findings, which made it possible to measure the level of trust and risk demonstrating compliance with the guidelines for implementing the budget. The basic requirements for the management of financial information are fully identified in the Manual of Technical Regulations of the budget and in the Code of Professional Planning and Public Finance; for this reason, the entity's financial statements are prepared and submitted in accordance with the regulations and technical accounting financial that emits the Ministry of Finance. The audit included a review on the basis of substantive evidence, compliance with the evidence that supports the information presented in the details of findings, in accordance with the basic requirements of management.